Effects of transdermal scopolamine, alone or in combination with cimetidine, on total 24 hour gastric acid secretion in patients with duodenal ulcer. Issue 12 (December 1986) - Richardson, C T; Feldman, M
Abstract : Transdermal scopolamine is an antimuscarinic preparation approved for use in the United States for prevention of motion sickness. A recent study using this drug (0.5 mg/patch) suggested that enough scopolamine was absorbed through the skin to reduce basal gastric acid secretion in patients with duodenal ulcer. We have compared the effect of transdermal scopolamine and oral cimetidine (400 mg twice daily) in seven men with chronic duodenal ulcer, both alone and in combination, on acid secretion throughout an entire 24 hour period in a placebo-controlled, randomised, double blinded cross over study. The effect of these drugs on basal, interprandial, and nocturnal gastric juice volume and hydrogen ion concentration also was measured. Transdermal scopolamine had no significant effect on mean 24 hour acid secretion (placebo, 409.4 mmol/day; scopolamine, 364.0 mmol/day) nor did it have a significant effect on gastric juice volume or hydrogen ion concentration. The combination of transdermal scopolamine plus cimetidine was not more effective than cimetidine alone in reducing total 24 hour acid secretion (mean, 231.8 versus 235.3 mmol/day) nor in reducing gastric juice volume or hydrogen ion concentration.